Pengaruh Marketing Mix Terhadap Keputusan Pembelian Produk Kecantikan Dengan Pendekatan Regresi Logistik Biner - Rendra Erdkhadifa; Bella Nureza Novariana (Al-Muraqabah: Journal of Management and Sharia Business, 2021)
Over the last years, the data indicate that in east java province, the population of women is larger than the population of men. This current condition is something that makes the business person who has a business in the field of cosmetics sell them. It cannot be denied, that cosmetics have been improving and growing rapidly. On another hand, this business gets into the emergence of business in the form of multi-level marketing. The faculty of economics and business Islam is faculty that has had female students as the majority. That’s why the researcher was so interested to analyze consumption patterns among the students related to the use of cosmetics. The method that is used in this research is binary logistic regression and the variables observed by the researcher are the decision of purchasing beauty products that are influenced by the marketing mix included of the product, price, promotion, and place of purchase of the product. With a sample of 440 respondents, the appropriate model in the results of the analysis is the second stage model and the results show that the variables that influence the decision of purchasing beauty products are the price and availability, and affordability of the place of purchasing beauty products.